Three new species of Acalypha L. (Euphorbiaceae, Acalyphoideae) from Tanzania and Angola and their conservation status - Iris Montero-Muñoz; José María Cardiel; Lucía Villaescusa-González; Pablo Muñoz-Rodríguez (PLoS ONE, 2025)
We describe Acalypha brevipetiolata and A. bracteolata from Tanzania, and A. linearis from Angola, as species new to science. We provide illustrations, distribution maps, and preliminary conservation assessments. We discuss their significance in the context of both countries and within the framework of an ongoing taxonomic monograph of the genus in Africa. These are the first new Acalypha species described in Africa in nearly two decades, in Tanzania in five decades, and in Angola in over a century.